Determinants of and future violations following deferred prosecution and non‐prosecution agreements in corporate criminal cases - De Franco, Gus; Small, R. Christopher; Wahid, Aida Sijamic (Contemporary Accounting Research, 2025)
Abstract The US Department of Justice's increasing use of deferred prosecution and non‐prosecution agreements (D/NPAs) over the past two decades has sparked debate about their merits compared with traditional plea deals, which often result in criminal convictions. This study examines the factors influencing prosecutors' decisions to use D/NPAs in disciplining firms for corporate misconduct. We analyze whether the likelihood of a firm's future misconduct varies by the type of discipline imposed, comparing the effectiveness of D/NPAs to traditional prosecution. Our findings reveal that prosecutors are more likely to employ D/NPAs with firms when a criminal conviction could cause significant economic harm to stakeholders. However, firms subject to D/NPAs are more likely to commit subsequent violations compared with those entering plea deals. As D/NPAs gain traction in the United States and internationally, our research highlights a trade‐off: while D/NPAs mitigate harm to innocent stakeholders, they are less effective at deterring future misconduct than traditional prosecutions.